Bleeding, death, and costs of care during hospitalization for acute pulmonary embolism: Insights from the Saint Luke's Outcomes of Pulmonary Embolism (SLOPE) study. (February 2021) - Bunte, Matthew C; Gosch, Kensey; Elkaryoni, Ahmed; Noman, Anas; Johnson, Erin; Jones, Philip; Indaram, Mahathi B; Vupputuri, Sravanthi
Limited data exist that comprehensively describe the practical management, in-hospital outcomes, healthcare resource utilization, and rates of post-hospital readmission among patients with submassive and massive pulmonary embolism (PE). Consecutive discharges for acute PE were identified from a single health system over 3 years. Records were audited to confirm presence of acute PE, patient characteristics, disease severity, medical treatment, and PE-related invasive therapies. Rates of in-hospital major bleeding and death, hospital length of stay (LOS), direct costs, and hospital readmission are reported. From January 2016 to December 2018, 371 patients were hospitalized for acute massive or submassive PE. In-hospital major bleeding (12.1%) was common, despite low utilization of systemic thrombolysis (1.8%) or catheter-directed thrombolysis (3.0%). In-hospital death was 10-fold higher among massive PE compared to submassive PE (36.6% vs 3.3%, p < 0.001). Massive PE was more common during hospitalizations not primarily related to venous thromboembolism, including hospitalizations primarily for sepsis or infection (26.8% vs 8.2%, p = 0.001). Overall, the median LOS was 6.0 days (IQR, 3.0–11.0) and the median standardized direct cost of admissions was 10, 032 (IQR, 4467–20, 330). Rates of all-cause readmission were relatively high throughout late follow-up but did not differ between PE subgroups. Despite low utilization of thrombolysis, in-hospital bleeding remains a common adverse event during hospitalizations for acute PE. Although massive PE is associated with high risk for in-hospital bleeding and death, those successfully discharged after a massive PE demonstrate similar rates of readmission compared to submassive PE into late follow-up.